1977
DOI: 10.1002/ajh.2830020204
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical “normal” and “abnormal” eosinophils in acute leukemias

Abstract: Eosinophilic leukocytes may accompany a great variety of disorders and different types of acute leukemias. The most striking morphologic feature of eosinophils is their specific granules, but morphology alone often is insufficient to differentiate normal from abnormal eosinophils. Cytochemically, the eosinophils were considered "normal" when they did not contain alkaline phosphatase, chloroacetate esterase, toluidine blue metachromasia, Astra blue positivity, and specific PAS-positive granules, but did have pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Contrary to the findings in acute lymphoblastic leukemia [18], eosinophils in eo sinophilic leukemia proved to be leukemic because those cells had an abnormal karyotype [19,20]. As was shown by cytochemical reactions [21], abnormal eosinophils in M4Eo are involved in the leukemic process.…”
Section: Discussionmentioning
confidence: 42%
“…Contrary to the findings in acute lymphoblastic leukemia [18], eosinophils in eo sinophilic leukemia proved to be leukemic because those cells had an abnormal karyotype [19,20]. As was shown by cytochemical reactions [21], abnormal eosinophils in M4Eo are involved in the leukemic process.…”
Section: Discussionmentioning
confidence: 42%
“…Within patients with eosinophilia, the clonal eosinophilia group showed significantly higher ECP levels (median, IQR) compared to those of the non-clonal eosinophilia groups (30. 15 However, in clonal eosinophilia vs. nonclonal eosinophilia groups there were no significant differences in the median levels of IL-5 ( Figure 2). Our results are not consistent with a previous study (9), in which IL-5 levels were much higher in clonal compared to non-clonal eosinophilia.…”
Section: Resultsmentioning
confidence: 94%
“…In AML-Eo cases eosinophils major atypia consists in positivity for naphthol-AS-chloroacetate esterase (NACE). This cytochemical feature is missing in eosinophils from normal or reactive conditions and most myeloid malignancies with eosinophilia (15). We investigated 6 patients with AML -3 patients with AML-M4 (FAB) and inv(16)/ t(16;16) and 3 patients with AML-M2 (FAB) and t(8;21).…”
Section: Discussionmentioning
confidence: 99%
“…In their morphological and cytochemical studies on eosinophils in acute leukaemia, several authors have suggested the involvement of eosinophils in ma lignant clones [5,6]. The presence of Auer bodies in eosinophils [3,14] and the observation of a marker chromosome overlapping the eosinophilic granules [8] also suggest its involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Though several morphological and cytochemical studies [5][6][7] as well as cytogenetic analyses [8,9] sug gested the involvement of eosinophils in leukaemic clones, the origin of eosinophils is still controversial [5]. In this paper, we present a case of AML associated with a remarkable eosinophilia in relapse.…”
Section: Introductionmentioning
confidence: 94%